2021
DOI: 10.1097/txd.0000000000001199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline for Solid Organ Donation and Transplantation During the COVID-19 Pandemic

Abstract: Background. The coronavirus 2019 (COVID-19) pandemic has disrupted health systems worldwide, including solid organ donation and transplantation programs. Guidance on how best to screen patients who are potential organ donors to minimize the risks of COVID-19 as well as how best to manage immunosuppression and reduce the risk of COVID-19 and manage infection in solid organ transplant recipients (SOTr) is needed. Methods. Iterative literature searches were conducted, the last being January 2021, by a team of 3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 104 publications
(185 reference statements)
0
13
0
1
Order By: Relevance
“…There is sufficient evidence to confirm the effectiveness and safety of COVID-19 vaccines in HRTs. [32][33][34][35][36] However, in our cohort, only 12 patients (13.6%) received COVID-19 vaccination. We found that the QoL of HTRs has significantly decreased since the COVID-19 outbreak compared to that in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient evidence to confirm the effectiveness and safety of COVID-19 vaccines in HRTs. [32][33][34][35][36] However, in our cohort, only 12 patients (13.6%) received COVID-19 vaccination. We found that the QoL of HTRs has significantly decreased since the COVID-19 outbreak compared to that in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Based on published literature, COVID-19 was assumed to have no significant impact on graft failure. 54 As ESKD patients are considered a population at risk, we assumed that they were offered vaccination as a priority group with 2 doses administered within 3 months. In the vaccination scenario, community infection rates were assumed to decrease to null in a linear fashion over a period of 6 months after the beginning of the vaccination campaign.…”
Section: Methodsmentioning
confidence: 99%
“…Während der COVID-19-Pandemie ist die Zahl der Nierentransplantationen weltweit deutlich zurückgegangen [ 77 , 78 ]. Die Behandlung von bereits transplantierten Patient:innen unter immunsuppressiver Medikation, die an COVID-19 erkranken, ist schwierig – sowohl im Hinblick auf die Modifikation der immunsuppressiven Therapie zum Erhalt der Transplantatfunktion wie auch im Hinblick auf die optimale Therapie von COVID-19 [ 77 , 79 81 ].…”
Section: Covid-19-pandemie Und Niereninsuffizienzunclassified